Evaluation of wound healing using a combination therapy of NSAID and an antioxidant on mice model - Biswas, Raisa Prapti (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.